MODIFIKASI KURSI PENUMPANG KERETA API EKONOMI YANG ERGONOMIS DENGAN METODE ERGONOMIC FUNCTION DEPLOYMENT (STUDI KASUS PADA KA LOGAWA YANG DIPRODUKSI DI PT. INKA) - Irma Puspitasari; R. Koekoeh K.W. (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2016)
Economic train is one of transportations that is often used by Indonesian people because it has an economical cost and a wide extent. However, economic passenger seat that exists so far is still inappropriate according to anthropometry’s user. In the process of designing, it is necessary to pay attention toward the ergonomic aspect together with anthropometry approach in order to produce seat design which is suitable with the passenger’s expectation and body size. The purpose of this study is to get an ergonomic passenger seat design and to get the appropriate seat based on Indonesian’s anthropometry. The process of this study consists of distributing questionnaire and measuring the anthropometry train user, then the result of the data is by making House of Quality EFD. The data showed a specification seat : high chair 390 mm, seat depth 400 mm, width of seats one passenger 400 mm, high backrest 840 mm, the angle backrest 1050 1150, wide backrest 430 mm, high armrest 190 mm, length of the armrest 300 mm, width of the footrest 42 mm, given a pouch / bag, the thickness of the cushion 100 mm, material cushion is polyurethane foam that material cover is polyvinyl chloride, color seats gray, seat position is not face to face, and material frame from stainless steel. The result of redesign of the train passenger seat might support the sitting posture of passenger in order to make them stay healthy and ideal, and the passenger seat might have more good appearance.